Education and Authoritarian Consolidation in Egypt post 2013 - Tarek, Rola (AUC Knowledge Fountain, 2023)
This paper examines how educational changes in school textbooks during a moment authoritarian rebuilding aim to politically demobilize students. This paper investigates how education is a sphere of influence for politics, and how authoritarian consolidation efforts manifest themselves in public and religious education. Focusing on the curricular and textbook changes in Egypt, and using secondary and primary sources the study traces the changing nationalist and religious narratives and how it aids in authoritarian rebuilding.